Oligopolistic competition among providers in the telecommunication industry: The case of Slovakia - Katarina Valaskova; Marek Durica; Maria Kovacova; Elena Gregova; George Lazaroiu (Administrative Sciences, 2019)
The issue of the paper is devoted to the oligopolistic market structure, which is a popular form of imperfect competition occurring in the current market economies. The main aim of the paper is to quantify the selected oligopolistic structure of the telecom industry in the Slovak market in the period 2013-2017. We subjected the oligopoly to concentration analysis of the market to quantify and assess the competitive environment in which mobile providers are operating. Market concentration was measured while using specific indicators of market concentration CR2, CR3, the Herfindahl-Hirschman Index, Lorenz curve, Gini coefficient, and coefficient of variation, using the information on total revenues of operators, the share of mobile operators on total revenues, number of active customers, and the penetration of SIM cards. The calculated values of the selected market concentration indices in the telecom sector proved that the mobile operators market is highly concentrated. The services that are offered by operators are not identical, and they are differentiated based on price, quality, availability, or the target group of customers. We also identified the entry barriers, which can be categorized to strategic, economic, technical, and time barriers. The Slovak telecom sector is an oligopoly where competitors offer slightly differentiated products; however, the competitive environment in which they operate is highly concentrated and competition needs to be regulated to achieve the sustainable development of the telecommunication sector.
Keywords: 350; oligopoly; market concentration; telecommunication industry